2020
DOI: 10.3390/scipharm88030035
|View full text |Cite
|
Sign up to set email alerts
|

Application of FTIR Spectroscopy and HPLC Combined with Multivariate Calibration for Analysis of Xanthones in Mangosteen Extracts

Abstract: Mangosteen, or Garcinia mangostana L., has merged as an emerging fruit to be investigated due to its active compounds, especially xanthone derivatives such as α -mangostin (AM), γ-mangostin (GM), and gartanin (GT). These compounds had been reported to exert some pharmacological activities, such as antioxidant and anti-inflammatory, therefore, the development of an analytical method capable of quantifying these compounds should be investigated. The aim of this study was to determine the correlation between FTIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The strong band at 3000–3500 cm −1 corresponds to the hydrogen bond of the hydroxyl groups. The weak absorption 2930 cm −1 corresponds with the methylene (CH 2 ) groups, 1640 cm −1 is given by CH 3 bending, 998 cm −1 is the bend absorption of C-OH stretching vibration, and 598 cm −1 indicates –CH=CH- bending [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The strong band at 3000–3500 cm −1 corresponds to the hydrogen bond of the hydroxyl groups. The weak absorption 2930 cm −1 corresponds with the methylene (CH 2 ) groups, 1640 cm −1 is given by CH 3 bending, 998 cm −1 is the bend absorption of C-OH stretching vibration, and 598 cm −1 indicates –CH=CH- bending [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was previously reported about the complex formation of budenoside/γ-CD. The last study findings suggest that cogrinding and coprecipitation resulted in the formation of an inclusion complex and that this influenced the particle diameter and particle surface [ 34 ]. Our study found that the crystallinity of α-M/γ-CD CX was 28.2%, while the intact α-M and γ–CD were 91.1% and 62.6%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by Tejamukti et al (2020) reveals that xanthone derivate contents can be determined using FTIR combined multivariate calibration of PLSR and PCR. Like flavonoids, a xanthone derivate also has various biological activities among others (Rivero and Garibay, 2019), such as antioxidant, analgesic, anti-inflammatory, antifungal, and anthelmintic activities (El-Kenawy et al, 2018).…”
Section: Activity and Quality Determinationmentioning
confidence: 99%